2003
DOI: 10.1038/sj.ejcn.1601541
|View full text |Cite
|
Sign up to set email alerts
|

Modifying children's food preferences: the effects of exposure and reward on acceptance of an unfamiliar vegetable

Abstract: Objective: The aim of this study was to evaluate two interventions (one reward-based and one exposure-based) for increasing children's acceptance of an unfamiliar vegetable compared with a no-treatment control. It was predicted that the exposure condition would increase liking for, and consumption of, the vegetable relative to either the reward or control group. Design: Using a randomized controlled design, participants were assigned to one of two intervention groups (exposure or reward) or to a no-treatment c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
376
6
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 506 publications
(418 citation statements)
references
References 37 publications
(42 reference statements)
28
376
6
4
Order By: Relevance
“…The Start Healthy Feeding Guidelines which were recently developed by an expert panel of pediatric health and nutrition professionals in response to the need for practical, evidence-based advice on introducing solid foods to infants and toddlers concluded that there was no evidence that supports the need to restrict or avoid any foods for weaned infants who are not at risk for allergies [38]. The present study suggests that by introducing a variety of fruits and vegetables, both within and between meals, infants might be more accepting of fruits and vegetables, the consumption of which is generally low in the pediatric population [28], and the acceptance of which is difficult to enhance beyond toddlerhood [39,40]. Because mothers were apparently unaware of changes in acceptance, they may give up too soon when introducing these foods [10,11].…”
Section: Discussionmentioning
confidence: 80%
“…The Start Healthy Feeding Guidelines which were recently developed by an expert panel of pediatric health and nutrition professionals in response to the need for practical, evidence-based advice on introducing solid foods to infants and toddlers concluded that there was no evidence that supports the need to restrict or avoid any foods for weaned infants who are not at risk for allergies [38]. The present study suggests that by introducing a variety of fruits and vegetables, both within and between meals, infants might be more accepting of fruits and vegetables, the consumption of which is generally low in the pediatric population [28], and the acceptance of which is difficult to enhance beyond toddlerhood [39,40]. Because mothers were apparently unaware of changes in acceptance, they may give up too soon when introducing these foods [10,11].…”
Section: Discussionmentioning
confidence: 80%
“…Liking and preferences were also related to likelihood of daily intake of both fruit and vegetables, and such taste preferences have repeatedly been shown to be a good predictor of food choices (Domel et al, 1996;Resnicow et al, 1997;Lien et al, 2002;Neumark-Sztainer et al, 2003;Bere and Klepp, 2004). Repeated exposure to many different kinds of fruit and vegetables at early age might be a good strategy to improve liking (Wardle et al, 2003;Patrick and Nicklas, 2005). Positive self-efficacy was a third personal factor related to daily intake of fruit and vegetables.…”
Section: Discussionmentioning
confidence: 92%
“…The aim of the Schoolgruiten Project was that all children should eat the piece of fruit or vegetable together in their own classroom. Apart from increasing availability and accessibility, this F&V scheme was also supposed to increase the children's exposure to F&V. Repeated exposure is an important determinant of taste preferences 23 .…”
Section: The Schoolgruiten Projectmentioning
confidence: 99%